Media-pedagogical competence of company-based training staff - Breiter, Andreas [Verfasser]; Howe, Falk [Verfasser]; Härtel, Michael [Verfasser] (My University, 2017)
"Opportunities to deploy digital media for the initiation and support of vocational teaching and learning pro-cesses are comprehensive and diverse. The associated challenges for company-based training staff are cur-rently being investigated within the scope of the BIBB research project DiMBA. This project is based on a model of media-pedagogical competence which is presented in this article." (author's abstract ; BIBB-Doku)
Medienpädagogische Kompetenz des betrieblichen Ausbildungspersonals
Keywords: P 3.2.1 Ausbilder; T 4.9 Pädagogik; Ausbilder; Medienpädagogik; Kompetenz; Medienkompetenz; Digitale Medien